Psychophysiological functions of elite athletes in different age groups - Korobeynikova, L. G.; Makarchuk, M. Y.; Korobeynikov, G. V.; Mischenko, V. S.; Zaprovitriana, O. Z. (International Journal of Physiology and Pathophysiology, 2018)
Effects of age-related peculiarities of elite athletes on their psycho-physiological state were studied at the stage of maintaining high results. Three groups of athletes of different age were examined. The first group consisted of athletes aged 18-20, the second group included athletes aged 21-25, and the third group-athletes aged 26-34. All of them were the members of Ukraine national team in Greco-Roman wrestling. It has been revealed that elite athletes of older age group differ from the younger ones by the presence of greater fatigue with simultaneous autonomy decline when forming strategies of sports activities and the perfect mechanism of autonomic reactions. Age-related deterioration in perception of visual information in elite athletes of older age group manifests itself in a significant lowering of productivity, efficiency, and speed compared with the groups of younger athletes. In addition, in elite athletes of older age group, a significantly higher level of tension of the autonomic regulation of the heart rate and more optimal activation of the sympathetic nervous system (as a division of the autonomic nervous system) were detected, compared with those in younger athletes.